2020
DOI: 10.3390/antiox9060550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the APE1 Redox Function Inhibitor E3330 in Non-Small Cell Lung Cancer Cells Exposed to Cisplatin: Increased Cytotoxicity and Impairment of Cell Migration and Invasion

Abstract: Elevated expression levels of the apurinic/apyrimidinic endonuclease 1 (APE1) have been correlated with the more aggressive phenotypes and poor prognosis of non-small cell lung cancer (NSCLC). This study aimed to assess the impact of the inhibition of the redox function of APE1 with E3330 either alone or in combination with cisplatin in NSCLC cells. For this purpose, complementary endpoints focusing on cell viability, apoptosis, cell cycle distribution, and migration/invasion were studied. Cisplatin decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…The knockdown of APE1 by RNA interference has been shown to induce apoptosis in human cancer cell lines 51 . Our data indicated that NO.0449-0145 treatment induced cell apoptosis in both A549 and NCI-H460 cells, consistent with the results reported for other APE1 inhibitors, such as APX3330, which induced apoptosis in multiple tumor cell lines 14 , 17 . Intriguingly, we also observed some NO.0449-0145 treated cells characterized by cytoplasmic swelling and plasma membrane bubbles, followed by plasma membrane rupture and the subsequent loss of intracellular contents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The knockdown of APE1 by RNA interference has been shown to induce apoptosis in human cancer cell lines 51 . Our data indicated that NO.0449-0145 treatment induced cell apoptosis in both A549 and NCI-H460 cells, consistent with the results reported for other APE1 inhibitors, such as APX3330, which induced apoptosis in multiple tumor cell lines 14 , 17 . Intriguingly, we also observed some NO.0449-0145 treated cells characterized by cytoplasmic swelling and plasma membrane bubbles, followed by plasma membrane rupture and the subsequent loss of intracellular contents.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated DNA repair activity has been correlated with cisplatin resistance 5 . A previous study showed that the co-incubation cells with APX3330 and cisplatin significantly decreased cell viability compared with cisplatin alone 17 . Our study showed that NO.0449-0145 treatment alone was able to overcome cisplatin resistance in A549-DDP cell and sensitize A549-DDP cells to cisplatin treatment, implying that the inhibition of APE1 by a small-molecule inhibitor may be used to overcome chemotherapeutic resistance in lung cancer treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several APE1 inhibitors have been generated and explored, which can specifically target either AP site cleavage activity [methoxyamine and APE1 inhibitor compound III (API3)] or redox regulation function (E3330 and Gossypol/AT101) of human enzyme (reviewed in Laev et al, 2017). A recent study demonstrated that the combination of cisplatin treatment with inhibition of the redox function of APE1 by E3330 decreased migration and invasion of lung cancer cells (Manguinhas et al, 2020). Another study showed that APE1 redox inhibitors in combination with cisplatin inhibit proliferation of bladder cancer cells more efficiently than cisplatin alone (Fishel et al, 2019).…”
Section: Aberrant Repair Of Interstrand Dna Cross-linksmentioning
confidence: 99%
“…In the present study, the elevated level of 8-oxo-dG was found in both the cell lines HCT-116 and HT-29 after the treatment of gliadin which was signi cantly masked by the pre-treatment of curcumin.Abasic sites, the DNA damage which is created by oxidative stress is mainly repaired via BER pathway by using APE1 enzyme along with other BER enzymes. APE1 is a multifunctional enzyme, along with its role in DNA base repair, cleaving of AP sites, it also helps in maintaining the cellular redox homeostasis by interacting and activating many key transcription factors like Nrf-2, AP-1, NF-κB, p53, HIF1α and others(Sarkar et al 2017;Thakur et al 2018;Manguinhas et al 2020). In the present study transcriptional and translational levels (expression pro ling) of APE1, endonuclease activity and its redox function were performed in HCT-116 and HT-29 cells in the presence of gliadin, curcumin and their combinations.…”
mentioning
confidence: 99%